2023
DOI: 10.1007/s00134-023-07239-w
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering heterogeneity in sepsis: a comparative analysis of subphenotypes

Rombout B. E. van Amstel,
Jason N. Kennedy,
Brendon P. Scicluna
et al.

Abstract: Purpose:The heterogeneity in sepsis is held responsible, in part, for the lack of precision treatment. Many attempts to identify subtypes of sepsis patients identify those with shared underlying biology or outcomes. To date, though, there has been limited effort to determine overlap across these previously identified subtypes. We aimed to determine the concordance of critically ill patients with sepsis classified by four previously described subtype strategies.Methods: This secondary analysis of a multicenter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…At best, we found only a moderate relationship between SRS gene-expression endotypes and plasma cytokine clusters, which reflects the findings from a recently published study 48 that also found limited overlap between clinical, inflammatory and gene-expression phenotypes. This study found a similar relationship between ARDS inflammatory phenotypes and SRS as we found between our sepsis cytokine clusters and SRS, likely reflecting different underlying mechanisms and processes contributing to the observed patient clusters.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At best, we found only a moderate relationship between SRS gene-expression endotypes and plasma cytokine clusters, which reflects the findings from a recently published study 48 that also found limited overlap between clinical, inflammatory and gene-expression phenotypes. This study found a similar relationship between ARDS inflammatory phenotypes and SRS as we found between our sepsis cytokine clusters and SRS, likely reflecting different underlying mechanisms and processes contributing to the observed patient clusters.…”
Section: Discussionsupporting
confidence: 86%
“…46 47 However, lack of heterogeneity of treatment effect in this study does not preclude plasma cytokine-based subphenotyping providing predictive enrichment for other treatments highlights the importance of collecting biological samples alongside clinical trials to investigate these relationships. At best, we found only a moderate relationship between SRS gene-expression endotypes and plasma cytokine clusters, which reflects the findings from a recently published study 48 that also found limited overlap between clinical, inflammatory and geneexpression phenotypes. This study found a similar relationship between ARDS inflammatory phenotypes and SRS as we found between our sepsis cytokine clusters and SRS, likely reflecting different underlying mechanisms and processes contributing to the observed patient clusters.…”
Section: Discussionsupporting
confidence: 86%
“…4 a, activation (green) and inactivation (red) of intra-cellular signaling pathways identified through gene expression studies are shown according to critical illness syndrome and the subclassification scheme used; evidently some approaches are more congruent than others. In a recent study van Amstel et al compared class outputs of several critical illness subtyping schemes within the same set of patients and identified relatively low to moderate overlap between clinical, biomarker, and transcriptomic data-based approaches 59 . Furthermore, several studies have identified that integrated subclassification approaches, for example those that combine biomarker and transcriptomic approaches, may be more informative than using a single approach alone [59 61 .…”
Section: Towards Consensus Endophenotypesmentioning
confidence: 99%
“…In a recent study van Amstel et al compared class outputs of several critical illness subtyping schemes within the same set of patients and identified relatively low to moderate overlap between clinical, biomarker, and transcriptomic data-based approaches 59 . Furthermore, several studies have identified that integrated subclassification approaches, for example those that combine biomarker and transcriptomic approaches, may be more informative than using a single approach alone [59 61 . Moreover, it is established that nearly half of the patients switch between gene-expression endotypes assigned on day 1 by day 3 among adults 62 and children 63 .…”
Section: Towards Consensus Endophenotypesmentioning
confidence: 99%
“…A summary of previous studies on sepsis subtypes is presented in Supplementary Material: Table S1 . Considering the complex and rapidly evolving characteristics of sepsis, cluster analysis based on multi-systematic and comprehensive time-series data of easily accessible clinical indicators is more consistent with the characteristics of sepsis, providing better classification [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%